2021
DOI: 10.1002/hbm.25730
|View full text |Cite
|
Sign up to set email alerts
|

The roles of the LpSTS and DLPFC in self‐prioritization: A transcranial magnetic stimulation study

Abstract: The Self-Attention Network (SAN) has been proposed to describe the underlying neural mechanism of the self-prioritization effect, yet the roles of the key nodes in the SAN-the left posterior superior temporal sulcus (LpSTS) and the dorsolateral prefrontal cortex (DLPFC)-still need to be clarified. One hundred and nine participants were randomly assigned into the LpSTS group, the DLPFC group, or the sham group. We used the transcranial magnetic stimulation (TMS) technique to selectively disrupt the functions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…A closer look at the consensus predictive network revealed that the FCs of several nodes within the DMN, SN, and DAN over the frontal and temporal lobes, such as the SFG, IFG, and STG, contributed signi cantly to the model. The involvement of these regions in self-related cognition has been repeatedly reported 6, 30,31 , and our results con rmed their roles in self-processing. In addition to these high-level cortices, the current ndings highlight the role of several subcortical structures, especially the FCs between the thalamus, insula, and amygdala.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A closer look at the consensus predictive network revealed that the FCs of several nodes within the DMN, SN, and DAN over the frontal and temporal lobes, such as the SFG, IFG, and STG, contributed signi cantly to the model. The involvement of these regions in self-related cognition has been repeatedly reported 6, 30,31 , and our results con rmed their roles in self-processing. In addition to these high-level cortices, the current ndings highlight the role of several subcortical structures, especially the FCs between the thalamus, insula, and amygdala.…”
Section: Discussionsupporting
confidence: 87%
“…The contributing FCs were further identi ed through analyses of model coe cients and computational lesions. Based on previous theoretical and empirical studies 1,8,28,29,30,31 , we hypothesized that the medial prefrontal cortex, posterior superior temporal sulcus, and dorsolateral prefrontal cortex would signi cantly contribute to the performance of the model. The roles of other regions were also examined using our data-driven approach.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of task‐based functional magnetic resonance imaging (fMRI) research has been devoted to studying the neural basis of the SPE, mainly focusing on brain regions. For example, it was suggested that the causal coupling between the medial prefrontal cortex (MPFC) and the left posterior superior temporal sulcus (LpSTS) facilitates information flow between regions sensitive to self‐relevant features (Liang et al, 2021; Sui et al, 2013; Yin et al, 2021). There is also evidence that besides the MPFC and adjacent areas, processing of self‐relevant information is associated with activity in lateral posterior areas, such as the inferior parietal lobule (IPL) (van der Meer et al, 2010), posterior cingulate cortex (PCC), bilateral angular gyrus (Yaoi et al, 2015) and anterior insular cortex (ACC) (Molnar‐Szakacs & Uddin, 2013; Perini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%